KEPEMILIKAN HAK ATAS TANAH DALAM KERANGKA POLITIK HUKUM AGRARIA NASIONAL - Widyarini Indriasti Wardani (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2018)
The development of ownership of land rights in Indonesia develops in line with the developments of the State of Indonesia itself. In this case includes four periods that each period has a specificity related to the political history of the nation. The period is the period of the Kingdom period, the period of the nation's occupation period foreigners namely the Netherlands and Japan, the period of Independence, and the period after the release of Law No. 5/1960 (Basic Agrarian Law). With the enactment of UUPA (National Agrarian Law), the ownership of land rights in Indonesia only differentiates ownership of land rights for Indonesian citizens and for foreign nationals by recognizing the rights of individual land that is Property rights, Building Use Rights, Usage Rights, use rights and the right to lease and title to communal land that is ulayat right (inherited from customary law).